Turkish Validation of Patient Satisfaction Towards Patient Oriented Pharmacy Services Questionnaire in Patients with Chronic Disease - OKUYAN, BETÜL; SANCAR, MESUT; AY, NADİYE PINAR (AVES PRESS LTD, 2016)
Objective: The aim of the study was to validate the Turkish version of the patient satisfaction questionnaire that evaluated satisfaction of patients with chronic diseases regarding pharmacy services. Methods: The present study was conducted between September 2015 and November 2015 among patients who had chronic diseases at least for 6 months and applied to community pharmacies. After appropriate language translation, pre-test, test-retest validity, and factor analysis were conducted. Results: The mean age of 154 patients (91 male, 63 female) was 58.6 +/- 13.8 years. The mean score of the Patient-Oriented Pharmacy Services Questionnaire (PSPSQ) 2.0 was 3.29 +/- 0.47, and the Cronbach's alpha coefficient was 0.944. A strong correlation was determined between the test-retest validity of the total and subscale scores (p<0.001). Three domains (quality of care, patient-pharmacist relationship, and overall satisfaction) were obtained in factor analysis of PSPSQ 2.0, as in the original study. Conclusion: In the present study, the Turkish form of PSPSQ 2.0 was determined to be a reliable and valid scale to assess patients' satisfaction regarding patient-oriented pharmacy services.
Keywords: Chronic disease; patient satisfaction; patient-oriented pharmacy services; Turkish validation